ChemInform Abstract: Annulation of 2H‐Pyran onto 1‐Oxa‐ or 1‐Azacyclohexane‐2, 4‐diones and Their Analogues via Sequential Condensation with α‐Substituted Enals and 6π‐Electrocyclization. Issue 46 (18th November 2014) - Hossain, Md. Imran; Shaban, Elkhabiry; Ikemi, Taku; Peng, Wei; Kawafuchi, Hiroyuki; Inokuchi, Tsutomu
Abstract Dihydropyrano[4, 3‐b]pyranone derivatives are prepared via a Knoevenagel condensation followed by a 6π‐electrocyclization.